Starch-based sodium percarbonate green oxygen release agent as well as preparation method and application thereof

Through the use of starch-based sodium percarbonate green oxygen release agent, the problem of excessive oxygen concentration in air conditioning packaging is solved, and the continuous and stable oxygen release of meat is achieved, which delays the deterioration of meat color, improves meat quality and reduces food safety risks.

CN119563704APending Publication Date: 2025-03-07CHENGDU INSTITUTE OF BIOLOGY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411779950.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Direct filling of oxygen in the atmosphere packaging may lead to excessive oxygen concentration, leading to intensified oxidation of meat fat, producing adverse flavors and affecting the texture of meat.

Method used

The starch-based sodium percarbonate green oxygen release agent is used to form a V-shaped crystal structure and combine it with sodium percarbonate to achieve the effect of continuous, stable and slow oxygen release.

Benefits of technology

This method can delay the deterioration of meat color in the food field, provide a local high oxygen concentration environment, improve the overall quality of meat, and avoid food safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005172541460000011
    Figure HDA0005172541460000011
  • Figure HDA0005172541460000012
    Figure HDA0005172541460000012
  • Figure HDA0005172541460000021
    Figure HDA0005172541460000021
Patent Text Reader

Abstract

The invention belongs to the field of preservatives, and particularly relates to a starch-based sodium percarbonate green oxygen release agent as well as a preparation method and application thereof. According to the technical scheme, the sodium percarbonate-starch composite crystal comprises a V-shaped crystal structure cavity formed by hydrophilic modified starch and fatty acid, and the V-shaped crystal structure cavity and sodium percarbonate form a stable composite crystal structure. The invention provides a novel green composite fresh-keeping oxygen slow-release agent, namely a sodium percarbonate-starch composite crystal, which can be used in multiple fields of food processing, medical treatment, environmental protection and the like, and is particularly suitable for application environments needing continuous and controllable high-concentration oxygen release.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preservatives, and in particular relates to a starch-based sodium percarbonate green oxygen-releasing agent and a preparation method and application thereof. Background Art

[0002] Meat preservation is directly related to meat quality, safety and shelf life. At present, meat preservation technologies mainly include low-temperature preservation, chemical preservation, physical preservation and biological preservation. Among them, low-temperature preservation is the most commonly used method, but improper temperature control may lead to the formation of large ice crystals and destroy the cell structure of meat; and over time, the color of meat will gradually become dull. Chemical preservation is the use of chemical substances such as preservatives and antioxidants to inhibit the oxidation and corruption of meat; this type of method has food safety issues and may pose potential health risks. Biological preservation is the use of natural bioactive substances or the metabolic activities of microorganisms to inhibit the corruption of meat. It is currently mainly used in specific types of meat processing and has a limited scope of application. Physical preservation includes vacuum packaging, modified atmosphere packaging, irradiation and other methods to extend the shelf life by changing the environmental conditions of meat. Vacuum packaging has additional equipment costs, and irradiation preservation may be restricted by laws and regulations, and may affect the taste of meat and reduce nutritional value.

[0003] In recent years, research on modified atmosphere packaging preservation technology has gradually increased. This technology improves the environmental composition of the package by filling or releasing a certain proportion of specific gas in the package, achieving the purpose of preservation and anti-corrosion, and extending the shelf life of the product.

[0004] Filling or slowly releasing appropriate oxygen in modified atmosphere packaging can help keep meat fresh. This is because: 1. The interaction between oxygen and oxymyoglobin. Oxymyoglobin in meat has a very high demand for oxygen. When the oxygen concentration is sufficient, oxymyoglobin can maintain a stable structure and function, keeping the meat bright red. If the oxygen concentration is insufficient, oxymyoglobin will be converted into metmyoglobin and deoxymyoglobin, causing the color of the meat to change from bright red to brown, affecting consumers' desire to buy. 2. Inhibit the growth of anaerobic bacteria. The growth of microorganisms is one of the main causes of meat spoilage. By increasing the oxygen concentration, the growth and reproduction of anaerobic bacteria can be inhibited, thereby helping to extend the shelf life of meat.

[0005] However, if oxygen is directly added to the modified atmosphere packaging, the initial oxygen concentration in the packaging will be too high. Excessive oxygen concentration may lead to increased oxidation of fat in meat, produce unpleasant flavors and cause changes in meat texture. Therefore, if a slow-release material can be provided to continuously, stably and slowly release oxygen so that the oxygen concentration in the package is continuously and stably maintained higher than the external value, it is expected to achieve a good meat preservation effect. Summary of the invention

[0006] The purpose of the present invention is to provide a starch-based sodium percarbonate green oxygen-releasing agent and a preparation method and application thereof.

[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a starch crystal, wherein the crystal includes a V-shaped crystal structure formed by starch and fatty acids, and the V-shaped crystal structure forms a composite crystal with sodium percarbonate.

[0008] Preferably, the crystals contain 30 to 60 parts of sodium percarbonate and 30 to 60 parts of starch by mass.

[0009] Preferably, the starch is high-amylose starch, and the amylose content is greater than 50%.

[0010] Preferably, the starch is modified by carboxymethylation.

[0011] Accordingly, the method for preparing the crystal comprises the following steps:

[0012] (1) dissolving one or more of sodium tripolyphosphate, sodium dodecylsulfonate, and polyacrylamide in a hydrogen peroxide solution;

[0013] (2) Add sodium carbonate and starch at 10-15°C;

[0014] (3) Add saturated fatty acid and sodium chloride and continue stirring for 20 to 30 minutes to allow crystallization.

[0015] Preferably, in step (1), one or more of sodium tripolyphosphate, sodium dodecylsulfonate and polyacrylamide is dissolved in a hydrogen peroxide solution at a mass fraction of 0.5 to 2% of hydrogen peroxide.

[0016] Preferably, in step (2), the pH of the reaction solution is controlled to be between 6.5 and 7.5, and sodium carbonate and starch are added to the hydrogen peroxide solution in batches.

[0017] Preferably, after the crystallization in step (3) is completed, centrifugation is performed, filtration is performed to remove moisture, and drying is performed.

[0018] Correspondingly, a fresh-keeping material is prepared using the crystal or the crystal obtained by the preparation method.

[0019] Accordingly, the method of continuously and controllably releasing oxygen using the crystal or the crystal prepared by the preparation method is particularly suitable for food preservation.

[0020] The present invention has the following beneficial effects: The present invention provides a new preservative: sodium percarbonate@starch composite crystal oxygen release agent, which can be applied to multiple application fields that require continuous and controllable high-concentration oxygen release, such as food processing, medical treatment and environmental protection. In the field of food, it is suitable for preserving meat, cold chain food and pre-prepared food, and can continuously and stably provide a local high-oxygen concentration environment to delay the color deterioration of meat.

[0021] When preparing starch-based sodium percarbonate oxygen-releasing agent, based on the principle of recrystallization of amylose and fatty acids, and introducing carboxymethyl groups into starch, the particle size of starch V-type crystals during crystallization can be increased, so that a cavity can be better provided for sodium percarbonate, thereby forming a stable V-type crystal structure encapsulating sodium percarbonate crystals. The hydrophilicity of starch is increased by low-substituted carboxymethyl modification, which can effectively slow down the process of water migration to sodium percarbonate crystals, thereby slowing down the rate of sodium percarbonate releasing oxygen, increasing the oxygen concentration on the surface of the oxygen-releasing crystal material, and effectively improving the oxygen slow-release effect of the composite crystal. Compared with the existing single oxygen-enriched layer oxygen-releasing material (sodium percarbonate), the crystal material prepared by the present invention is more superior in color protection and preservation.

[0022] Compared with the popular oxygen-permeable film tray packaging and high-oxygen (80% O2) inflatable packaging on the market, the present invention can adjust the oxygen concentration in the package by controlling the amount of oxygen-releasing material (sodium carbonate@starch crystals) embedded in the oxygen-rich layer, thereby adapting to different application scenarios. In addition, the embedding method can also prevent the oxygen-releasing material from directly contacting the food surface, avoiding food safety issues.

[0023] In summary, the preparation method of the oxygen-releasing material provided by the present invention is simple and practical, can help preserve the freshness of meat, and contribute to improving the overall quality of meat. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the microscope image of SPC@HA-CS;

[0025] Figure 2 This is a microscope image of SPC@HA;

[0026] Figure 3 This is a comparison chart of the oxygen release capacity of SPC, SPC@HA and SPC@HA-CS;

[0027] Figure 4 This is a comparison chart of the oxygen release capacity of SPC and SPC@HA-CS in meat preservation;

[0028] Figure 5 This is a comparison chart of the effects of SPC and SPC@HA-CS on beef pH;

[0029] Figure 6This is a comparison chart of the effects of SPC and SPC@HA-CS on beef cooking loss rate;

[0030] Figure 7 This is a comparison chart of the color changes of the front side (not in contact with the oxygen-rich layer) and the back side (in contact with the oxygen-rich layer) of each group of beef at different times;

[0031] Figure 8 This is a comparison chart of the brightness and redness values ​​of the front and back sides of each group of beef;

[0032] Fig. 9 This is a comparison chart of the changes in the content of beef myoglobin in each group;

[0033] Fig.10 This is a comparison chart of the changes in malondialdehyde content in each group of beef. DETAILED DESCRIPTION

[0034] The invention provides sodium percarbonate@starch, which is a new starch crystal capable of enriching and slowly releasing oxygen.

[0035] The sodium percarbonate @ starch includes a V-shaped crystal structure formed by starch and fatty acids, and further forms a composite crystal with sodium percarbonate. In the sodium percarbonate @ starch crystal material, by weight, 30 to 60 parts of sodium percarbonate and 30 to 60 parts of starch. The preferred scheme is: the starch is a high-amylose starch (amylose content>50%, w / w); the starch is chemically modified, preferably carboxymethylated, to increase the hydrophilicity of the starch, so that it is easier to disperse and dissolve before forming crystals, providing a basis for subsequent crystallization.

[0036] The present invention also provides a method for preparing the starch-based sodium percarbonate green oxygen-releasing agent, comprising the following steps:

[0037] 1. Commercially available or prepared starch, preferably chemically modified starch, more preferably sodium carboxymethyl starch with a low degree of substitution (degree of substitution is 3-6%). An optional preparation method is: add 0.5-0.7g of monochloroacetic acid to 74mL of anhydrous ethanol, stir evenly and heat to 40-50°C until the monochloroacetic acid is completely dissolved, then add 12g of starch and stir evenly. Then add 0.1-0.3mL of 50% sodium hydroxide solution, heat to 70-85°C and keep warm for 10-30min. Then cool naturally, and when the sample drops to 30-40°C, add glacial acetic acid to adjust the sample pH to neutral, pour off the supernatant, and wash the precipitate with 80%-100% ethanol / methanol several times to obtain sodium carboxymethyl starch.

[0038] 2. In 15 mL of hydrogen peroxide solution (concentration 30-50%), dissolve 0.5-1.5% of the mass of hydrogen peroxide solution of one or more of sodium tripolyphosphate, sodium dodecylsulfonate, and polyacrylamide as stabilizers.

[0039] 3. At 10-15°C, add 4.5g sodium carbonate and 4g starch / modified starch in batches to induce slow crystallization. The addition should be completed within 20-30 minutes to avoid long-term reaction that may lead to decomposition of the formed sodium percarbonate.

[0040] 4. Maintaining 10-15°C, add 2-3g of saturated fatty acid and 0.3-0.4g of sodium chloride. It is preferred to use shorter chain (C10-C16) saturated fatty acids, such as C12:0 (lauric acid) and C16:0 (palmitic acid). After the addition is completed, continue stirring for 20-30 minutes to induce crystallization to slowly form, and obtain sodium percarbonate@starch composite crystals.

[0041] 5. After the crystallization is completed, centrifuge as soon as possible, filter to remove excess water in the crystal material, and dry it in an oven at 50-80°C for 2-4 hours to obtain sodium percarbonate@starch composite crystal powder.

[0042] Low-substituted sodium carboxymethyl high-amylose starch has good solubility and hydration; it has lower viscosity than highly substituted ones. It reacts with fatty acids to form a stable complex with a V-shaped crystalline structure in the starch double helix structure, and the gelatinization temperature is greater than 100°C.

[0043] The V-shaped crystal structure formed when fatty acids combine with starch provides an ideal wrapping space for the sodium percarbonate crystals formed at the same time, promoting the formation of composite crystals and making the sodium percarbonate@starch composite crystals more stable.

[0044] Since carboxymethyl high-amylose sodium starch is hydrophilic, when the sodium percarbonate@starch composite crystals meet water, both the starch and the sodium percarbonate crystals will absorb water. Since the modified starch has a stronger water absorption capacity, it can compete with the sodium percarbonate crystals for water, thereby slowing down the migration of water to the sodium percarbonate crystals. Moreover, this process will avoid the rapid hydrolysis of sodium percarbonate, thereby adjusting the release rate of oxygen, so that oxygen is released slowly and continuously. Moreover, it can also more effectively embed sodium percarbonate, thereby reducing the direct contact of sodium percarbonate with air or water, avoiding the excessive release of oxygen, which is conducive to controlling its release rate.

[0045] In addition, the oxygen released by sodium percarbonate will be enriched in the cavity of the composite crystal, thereby further increasing the oxygen concentration on the surface of the composite crystal oxygen-releasing material. This oxygen enrichment phenomenon helps to maintain the stability of oxygen release and prolong the duration of oxygen release, thereby providing a more lasting effect for fresh-keeping applications.

[0046] The embedding treatment is used to isolate the sodium percarbonate@starch composite crystals from the food, which not only prevents the oxygen-releasing material from directly contacting the food, but also reduces the potential food safety risks. This design not only ensures food safety, but also optimizes the control of oxygen release, avoiding the premature release of oxygen during storage or use, and provides a new solution for food preservation.

[0047] In summary, the sodium percarbonate@starch composite crystals can be stably stored for a long time in a dry environment. After contacting with moisture, they will slowly release oxygen, adjust the pH, and have a certain preservative effect. Therefore, they can be used in places where slow release of oxygen is required, such as for the preservation of cold chain foods and pre-prepared foods, and for the preservation of color, moisture and tenderness of meat.

[0048] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. The data obtained are all average values ​​obtained after at least 3 repetitions, and all the data obtained in each repetition are valid data.

[0049] Example 1: Preparation of sodium percarbonate@starch composite crystals

[0050] 1. Preparation of low-substituted sodium carboxymethyl starch: Add 0.6g of monochloroacetic acid to 74mL of anhydrous ethanol, stir evenly and heat to 50°C, then add 12g of high-amylose starch and stir evenly. Add 0.15mL of 50% sodium hydroxide solution, heat to 81°C and keep warm for 15 minutes. Then cool naturally, and when the sample drops to 40°C, add glacial acetic acid to adjust the pH of the sample to neutral, pour off the supernatant, and wash the precipitate with 80% ethanol several times to obtain sodium carboxymethyl starch.

[0051] In 15mL hydrogen peroxide solution (concentration of 30%), evenly dissolve 0.5% sodium tripolyphosphate by weight of hydrogen peroxide. Then at 15°C, add 4.5g sodium carbonate and 4g sodium carboxymethyl starch in small batches and add them within 20 minutes. Then add 2.5g lauric acid and 0.4g sodium chloride. Continue stirring for 30 minutes to induce crystallization to slowly form. After the crystallization is completed, centrifuge, filter, and dry in an oven at 55°C for 2 hours to obtain sodium percarbonate @ sodium carboxymethyl starch crystalline powder, SPC@HA-CS.

[0052] 2. Set up control group 1: only use an equal amount of sodium percarbonate, SPC; control group 2: other conditions are the same, use an equal amount of unmodified straight-chain starch instead of sodium carboxymethyl starch to prepare a crystalline powder, SPC@HA.

[0053] 3. Microscope images of SPC@HA-CS and SPC@HA Figure 1 , 2 shown. Figure 1 , 2 In the figure, A, C, E, and G are unpolarized images, and B, D, F, and H are polarized images. The results show that carboxymethyl-modified amylose has a better effect of embedding sodium percarbonate as a wall material, which is more conducive to obtaining stable sodium percarbonate@starch crystals; for starch that has not been carboxymethyl-modified, it can be observed that the formed complex crystals are outside the starch granules and do not form stable inclusions.

[0054] 4. Test the oxygen release capacity of SPC, SPC@HA and SPC@HA-CS respectively. The test method is as follows: put 6g of SPC, SPC@HA and SPC@HA-CS into 6×8cm transparent packaging bags respectively, add 10mL of water, and seal them at room temperature. The initial oxygen concentration in the packaging is 20%. After 24h and 48h, insert the oxygen meter probe into the packaging box for detection. Set 3 replicates for each sample and take the average value of the results. The results are as follows: Figure 3 shown.

[0055] The results showed that SPC can release oxygen quickly, and both SPC@HA and SPC@HA-CS have a certain ability to slowly release oxygen. The oxygen release of SPC@HA-CS was similar to that of SPC@HA at 4 hours, but at 24 hours, the oxygen release of SPC@HA-CS increased and gradually approached that of SPC. Therefore, compared with SPC@HA, SPC@HA-CS has a higher oxygen release and better oxygen release persistence, and is more suitable for occasions that require high oxygen concentration and long-term maintenance of oxygen concentration.

[0056] Example 2: Demonstration of the preservation effect of sodium carbonate@starch composite crystals

[0057] 1. The SPC and SPC@HA-CSP prepared in Example 1 were packaged using food-grade DuPont paper materials. 6 g of oxygen-releasing material samples were placed in transparent packaging bags, and a sponge of the same size that had been pre-absorbed with 10 mL of water was placed at the bottom of the oxygen-releasing packaging material. Three oxygen-enriched layer embedding materials were prepared. The fiber structure of food-grade DuPont paper materials is fine, so that liquid water and oil cannot easily penetrate. At the same time, DuPont paper has good gas and water vapor permeability.

[0058] Under sterile conditions, fresh beef slaughtered on the same day was cut into uniform-sized slices (4×4×1 cm), placed on different oxygen-enriched layer embedding materials (4×4 cm), sealed in food-grade packaging bags, and stored in a refrigerator at 4°C. A blank group was also set up: the other conditions were the same, and no oxygen-enriched material was embedded in the DuPont paper.

[0059] 2. The appearance (color) of the beef in each group was observed at 0d, 1d and 2d, and the oxygen concentration, pH, cooking loss rate, myoglobin content and malondialdehyde content in the packaging bags of each group were measured. Three replicates were set for each group, and the results were averaged.

[0060] (1) Oxygen concentration detection: Insert the oxygen meter probe into the packaging box for detection. Figure 4 The results showed that the oxygen concentration in the SPC@HA-CSP group continued to rise to 50-60%, and then the concentration remained relatively stable; the oxygen concentration in the SPC group dropped significantly on the second day. The oxygen concentration in the blank group without an oxygen-enriched layer continued to drop.

[0061] (2) Beef pH test: Take out the sample, chop it into small pieces, then add it into a distilled water solution (meat: water = 1:10, w / w), use a homogenizer to homogenize it, and then measure the pH of each solution. Figure 5 shown.

[0062] The initial pH of fresh beef was 6.26, and the pH of beef in all groups increased from day 1. This may be because spoilage bacteria degraded proteins and produced amines and organic sulfides after exhausting the glucose in the meat, which led to an increase in the pH of beef. The pH of beef in the SPC group was the highest overall, which may be because the sodium percarbonate obtained by the decomposition of pure sodium percarbonate without encapsulation increased the pH of the meat. The pH of beef in the SPC@HA-CS group also increased, but compared with the SPC group and the blank group, the pH of beef in the SPC@HA-CS group increased the least due to its encapsulation effect on sodium percarbonate. This may be because SPC@HA-CS may have a slow-release property, which means that it can release oxygen and decomposition products, including alkaline substances, more slowly. This slow release may reduce its rapid impact on pH. The pH of beef in the SPC@HA-CS group increased more gently and steadily, which is more conducive to the preservation of meat quality.

[0063] (3) Analysis of beef cooking loss rate:

[0064] Cooking loss rate: Take a beef sample, remove the muscular membrane and fat visible on the surface, and cut it into strips of approximately 2cm×1cm×1cm. Weigh the mass of the meat strips (m1), put them into a ziplock bag, seal them, and record them by number. Heat the meat in a constant temperature water bath, and start timing when the temperature reaches 75°C. After 40 minutes, take out the beef sample from the ziplock bag and cool it to room temperature. Use filter paper to absorb the moisture on the surface and weigh the mass again (m2). Cooking loss rate = 100% × (m1-m2) / m1. The results are as follows: Figure 6 shown.

[0065] The results showed that after storage, the cooking loss rate of beef in each group increased, indicating that the water retention of beef gradually decreased during storage. Compared with other groups, the SPC@HA-CS group showed a better effect in reducing the cooking loss rate after longer storage.

[0066] (4) Analysis of beef surface color: Meat color is an important indicator for evaluating beef quality. When consumers buy raw meat, they often judge the quality of meat based on meat color. In fully bled muscle, meat color is mainly determined by the content and presence of myoglobin.

[0067] Each group of beef was observed with the naked eye and photographed; a colorimeter was used to detect the color change of beef. The moisture on the surface of the beef was dried, and the sample was placed directly under the light source. A transparent polyvinyl chloride cling film was covered on the surface of the beef sample, and the brightness value (L*) and redness value (a*) of the sample were measured with a portable colorimeter.

[0068] The color changes of the non-oxygen-rich layer contact surface (front) and the oxygen-rich layer contact surface (back) of each group of beef at different times (photographed) are shown in Figure 2. Figure 7 shown. Figure 7 From top to bottom, they are storage 0d and 1d. The changes in the brightness value (L*) and redness value (a*) of the front and back of each group of beef are shown in the figure. Figure 8 shown.

[0069] from Figure 7 It can be seen that compared with the color of the front side that is not in contact with the oxygen-rich layer, the beef in the SPC@HA-CS group and the SPC group that are in contact with the oxygen-rich layer (back side) are both redder and visually appear fresher. In the process of releasing oxygen, the sodium percarbonate@starch composite crystals will form oxygen enrichment in the cavity inside the crystals. This enrichment effect can significantly increase the oxygen concentration on the surface of the oxygen-releasing material. When the bottom of the beef comes into contact with this oxygen-rich oxygen-releasing material, its surface color may become brighter red. This phenomenon not only helps to maintain the bright red color of the beef, but also has positive significance for solving the problem of the bottom color deterioration of beef in the market due to contact with packaging materials during the sales process. By utilizing the characteristics of sodium percarbonate@starch composite crystals as oxygen-releasing materials, the color of the non-oxygen-rich layer contact surface of the beef surface (high oxygen environment) and the oxygen-rich layer contact surface of the bottom of the beef (oxygen-enriched environment) can be effectively protected, thereby improving the market competitiveness of beef.

[0070] according to Figure 8Compared with the initial value, the blank group and SPC@HA-CS both obtained a larger L* on the first and second days. Moreover, the L* values ​​of the beef color in the blank group and SPC@HA-CS on the front side showed a trend of first rising. Among them, the L* values ​​of the blank group on both the front and back sides were the highest, which may be related to the formation of more deoxymyoglobin in low-oxygen packaging, resulting in darker meat color.

[0071] a* is an important indicator of meat color. A high a* value indicates a high proportion of oxymyoglobin in fresh meat. During the entire storage process, the increase in a* value will be more conducive to the formation of the bright red color that consumers like. Figure 8 It was observed that the a* values ​​of all samples increased on the first day, which may be due to the combination of oxygen with myoglobin in fresh meat to form oxymyoglobin, which makes the meat red. However, as the storage time increases, the a* values ​​of each group decrease significantly. This may be due to the oxidation of myoglobin to alpha-myoglobin caused by microbial growth, resulting in a significant reduction in red color. However, compared with the blank group, the a* value of the group with oxygen-releasing material is high. This phenomenon shows that the addition of oxygen-releasing material helps to maintain the red color of the meat, and the slow-release oxygen effect of SPC@HA-CS further improves this effect. The a* value fluctuation of the beef on the contact surface with the oxygen-rich layer during storage is greater than the a* change on the front side of the beef, indicating that the beef on the contact surface with oxygen has a better color protection effect, which can better improve the problem that the meat color at the bottom of the fresh meat storage box is easy to deteriorate.

[0072] (5) Analysis of myoglobin content: Myoglobin is a complex protein, purple-red in color. It can combine with oxygen to form oxymyoglobin, which is bright red and is a symbol of fresh meat. Myoglobin and oxymyoglobin can both be oxidized to form metmyoglobin, which is brown and will darken the meat. Deoxymyoglobin is purple-red and will be oxidized to metmyoglobin after being left in the air for half an hour, causing the meat to darken and appear reddish brown.

[0073] The determination method is: extract myoglobin with cold 0.04mol / L, pH=6.8 phosphate buffer, the ratio of sample to buffer is 1:10 (m / V). The sample homogenate is centrifuged at 5°C, 50000g for 30min, and the supernatant is aspirated to measure its absorbance at 525, 545, 565 and 572nm wavelengths. The percentage of different forms of myoglobin is obtained by the following formula:

[0074] Total (mmol / L / L): -0.166A 572 +0.086A 565 +0.088A 545 +0.099A 525 ;

[0075] Oxygenated myoglobin content (MbO2) / % = (0.882R1-1.267R2+0.809R3-0.361) × 100;

[0076] MetMb content (MetMb) / % = (-2.54l R1 + 0.777R2 + 0.800R3 + 1.098) × 100;

[0077] Deoxymyoglobin content (deoxyMb) / % = (0.369R1+1.14R2-0.941R3+0.015)×100;

[0078] Where: R1, R2 and R3 are A 572 / A 525 , A 565 / A 525 and A 545 / A 525 .

[0079] The results are as follows Fig. 9 The results showed that the content of oxymyoglobin in beef from the SPC@HA-CS group was the highest among the three groups, which may be because the high concentration of oxygen conditions promoted the reaction of myoglobin with oxygen. At the same time, the content of deoxymyoglobin in the SPC@HA-CS group was the lowest among the three groups, indicating that SPC@HA-CS delayed the conversion of oxymyoglobin to deoxymyoglobin, which was conducive to maintaining the bright red color of the meat.

[0080] (6) Analysis of malondialdehyde content: Oxygen is one of the necessary conditions for lipid oxidation and can accelerate the formation of lipid peroxides, thereby generating oxidation products such as malondialdehyde. Lipid oxidation promotes the oxidation of myoglobin, which causes meat discoloration, further affecting the color change of beef during storage.

[0081] Assay method: Muscle sample (5 g) was mixed with 15 mL 5% trichloroacetic acid (TCA) and homogenized in an ice-water bath (13500 r / min) for 30 seconds. The mixture was filtered with filter paper, 2 mL of the filtrate was mixed with 2 mL 0.02 M thiobarbituric acid (TBA), 100°C water bath for 40 min, and then cooled to room temperature. The absorbance was read at 532 nm and the results were obtained in the standard curve.

[0082] Method for drawing a standard curve: Prepare a malondialdehyde (MDA) standard solution, dissolve 0.315g of 1,1,3,3-tetraethoxypropane and dilute to 1000mL (100μg MDA / mL), take 10mL of the solution and accurately dilute to 100mL (10μg MDA / mL). Mix 0.0mL, 0.1mL, 0.2mL, 0.3mL, 0.4mL, 0.5mL and 0.6mL of MDA (10μg MDA / mL) standard solution with 5% TCA solution to 5mL, and then mix with 5mL TBA solution. Read the absorbance at 532nm, summarize and draw a standard curve.

[0083] The results are as follows Fig.10 As shown. The results showed that in the group with oxygen-releasing materials added, the content of malondialdehyde, a product of lipid oxidation in beef, increased as a whole over time. This may be because the high oxygen environment promotes lipid oxidation reactions. Compared with the SPC group, the content of malondialdehyde in beef in the SPC@HA-CS group decreased significantly. This may be because SPC@HA-CS has a slow-release property, which means that it can release oxygen more slowly and evenly, avoiding the rapid changes in oxygen concentration that may be caused by SPC, thereby reducing oxidative stress. Lipid oxidation is one of the main causes of meat deterioration. The reduction of malondialdehyde means a reduction in harmful substances in beef, thereby improving food safety, helping to maintain the original flavor and taste of meat, and extending the shelf life of meat.

[0084] The embodiments described above are only descriptions of the preferred modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various deformations, modifications, and substitutions made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A starch crystal, characterized in that: The crystals include a V-shaped crystal structure formed by starch and fatty acid, and form composite crystals with sodium percarbonate.

2. The crystal according to claim 1, characterized in that: The crystals contain 30 to 60 parts of sodium percarbonate and 30 to 60 parts of starch by mass.

3. The crystal according to claim 1, characterized in that: The starch is high-amylose starch, and the amylose content is greater than 50%.

4. The crystal according to claim 1, characterized in that: The starch is modified by carboxymethylation.

5. The method for preparing the crystal according to any one of claims 1 to 4, characterized in that: The steps include: (1) dissolving one or more of sodium tripolyphosphate, sodium dodecylsulfonate, and polyacrylamide in a hydrogen peroxide solution; (2) Add sodium carbonate and starch at 10-15°C; (3) Add saturated fatty acid and sodium chloride and continue stirring for 20 to 30 minutes to allow crystallization.

6. The preparation method according to claim 5, characterized in that: In step (1), one or more of sodium tripolyphosphate, sodium dodecylsulfonate and polyacrylamide is dissolved in a hydrogen peroxide solution at a mass fraction of 0.5 to 2% of hydrogen peroxide.

7. The preparation method according to claim 5, characterized in that: In step (2), the pH of the reaction solution is controlled to be between 6.5 and 7.5, and sodium carbonate and starch are added to the hydrogen peroxide solution in batches.

8. The preparation method according to claim 5, characterized in that: After the crystallization in step (3) is completed, centrifuge, filter to remove water, and dry.

9. A fresh-keeping material prepared using the crystals according to any one of claims 1 to 4 or the crystals obtained by the preparation method according to any one of claims 5 to 8.

10. A method for sustained and controllable oxygen release using the crystal according to any one of claims 1 to 4 or the composite crystal prepared by the preparation method according to any one of claims 5 to 8.

Citation Information

Cited By

  • Autotrophic denitrification nitrogen removal filler suitable for sewage with low carbon-nitrogen ratio and preparation method of autotrophic denitrification nitrogen removal filler

    CN119874036A